Joint Management System for the Baomata Spring Area in Kiwangona Village, East Adonara District, East Flores Regency - Anastasia Desi Wolo; Mikael Samin; Poppy Haryany (Tinta Emas Institute, 2025)
Lack of public awareness in maintaining springs and the environment around springs can affect water quality, water availability, and ecosystems. The objectives of this study are (1) To determine the joint management system of the Baomata spring area in Kiwangona Village, East Adonara District, East Flores Regency (2) To determine the environmental aspects that are managed jointly in the management of the Baomata spring area (3) To determine the form of environmental preservation in the Baomata spring area. The method used in this study is a descriptive study through a qualitative approach. The results of the study show that (1) the management system of the Baomata spring area uses local wisdom with mutual cooperation (gemohing) (2) environmental aspects that are managed jointly include maintaining biodiversity, erosion control, and wise land use around the spring area (3) environmental preservation in the spring area in Kiwangona Village in the form of implementing customary rules, reforestation activities, and restrictions on land use. This is done to protect the spring and the forest area around the spring. The conclusion of this study is that joint management based on local wisdom is able to maintain the sustainability of the Baomata spring as the main source of clean water for the Kiwangona Village community, while strengthening social participation in maintaining the ecosystem.